PEMANFAATAN INTERNET SEBAGAI SARANA PENDUKUNG PENDIDIKAN DI PERGURUAN TINGGI - Eka Prastya; Didi Achjari (Akuntansi dan Teknologi Informasi, 2008)
The use of internet perticulary in higher education has been pervasive. The current study examines some factors that can affect accounting students' internet uses. The research model includes Internet Usage as the dependent variable. Meanwhile, the independent variables are Instruction of Lecturer, Availability, Outcome Expectations, and Internet Self-Efficacy. The study employed questionnaire survey that was administered to 128 undergraduate students at Accounting Department Universitas Gadjah Mada. The results of this study suggest that Instruction of Lecturer, Availability, and Internet Self-Efficacy, are the antecedents of Internet Usage. Unfortunately, the current research indicates a weak support toward Outcome Expectations. In conclusion, despite of abundant benefits of the internet, university students may not be interested to use it unless the lecturers ask them to do so and university provides the facilities. Students' Self-Efficacy also plays an essential role in the Internet Usage.